ALAT BANTU UNTUK PEMBUATAN ULIR LUAR DAN ULIR DALAM - Widodo Widodo (Jurnal Rekayasa Mesin, 2022)
The machining process is the process in which different products are made especially from metal and it is often used in both small and large industries. One of the products of the machining process is threaded products and there is an ongoing increase in the use of these products because of their ease of maintenance and assembly to a complete product. The manufacturing of these products can be done by several methods e.g., by using machine tools or hand taps. In line with that, to manufacture these products in large volumes and to achieve high production speeds, special supporting tools are required. The design of the supporting tools is evolving continuously because a single tool cannot fulfill the entire manufacturing process. To design and manufacture supporting tools, apart from the design, the safety and comfort aspects of work are also taken into account. The methodology for the manufacturing of this product is to use the design for manufacturing and assembly (DFMA) method, which starts with reviewing and identifying needs, designing and making these tools that are adapted to the standard tap/one dimension specifications and the type of material used is cast carbon steel. Based on the study of von misses for 32 N, 64 N, and 94 N loads, the results were 1.807 e+05, 3.614e+05 N/m2, 5.646e+03 N/m2, and this value is still below the stress value. The yield is 2.48168e+008 N/m2, therefore the type of material used is very safe for the manufacture of this product.